Feasibility study of utilising electronic nose to detect BSR disease in oil palm plantation - Marni Azira Bt Markom
This thesis is the work conducted on utilising electronic nose incorporating artificial intelligence to detect plant malaise, specifically, basal stem rot (BSR) disease that is caused by Ganoderma boninense, a type of fungi affecting oil palm plantations in South East Asia.